Panikachu (Calocasis esculenta L. Schott) cultivation in some selected areas of Bangladesh: an agro-economic profile - Haque, MA; Miah, MA Monayem; Hossain, S; Luna, AN (Bangladesh Journal of Agricultural Research, 2013)
Panikachu is a nutritious vegetable contributing to the total supply of vegetables during the summer in Bangladesh. Many farmers cultivate this crop from their innovative ideas. Researchers are unable to formulate adequate research design for its varietal improvement and technology packages. Therefore, the study was conducted in two panikachu growing districts, namely Joypurhat and Jessore during February 2011 to know the profitability of panikachu cultivation. In total, 100 panikachu farmers were selected of which 50 farmers from each area were selected randomly to collect primary data. The results indicated that the costs of panikachu cultivation were Tk. 2,67,726 and Tk. 1,84,530 per hectare on total cost and variable cost basis, respectively. The major share of total cost was for human labour (45%), land use (17%), and fertilizer (15%). The yield for rhizome and stolon were 24.94 tons and 23.29 tons per hectare. The gross margin and net returns were Tk. 2,06,058 and Tk. 1,22,862 per hectare. The benefit cost ratios was 1.46. Human labour, manure, urea, TSP, MoP, insecticides, and irrigation had positive effect on the yield of panikachu. Lack of technical knowledge about improved cultivation practices, non-availability of HYV seedling, and low price of product were major constraints to panikachu cultivation. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16977 Bangladesh J. Agril. Res. 38(3): 505-513, September 2013